2018
DOI: 10.1055/a-0583-3850
|View full text |Cite
|
Sign up to set email alerts
|

Standards in der Nachbehandlung nach vorderem Kreuzbandersatz im deutschsprachigen Raum

Abstract: Rehabilitation protocols differ significantly even among experienced knee surgeons working as instructors. Their recommendations are often not evidence-based considering the current literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
1
0
0
3
Order By: Relevance
“…Rather, early weight bearing seemed to improve the quadriceps muscle function and reduce the risk for patellofemoral pain [ 21 , 23 , 29 , 30 ], which is particularly associated with the choice of BTB grafts [ 6 , 10 ]. However, the DGOU tend to delay full weight bearing after ACLR for two weeks, similar to the survey’s results (ACLR-HAM: 2.0 ± 1.1 weeks; ACLR-BTB: 1.2 ± 0.7 weeks) [ 19 , 31 ], whereas the MOON Guidelines recommend immediate weight bearing after ACLR and so does the KNGF, as long as the gait pattern is correct [ 21 , 22 ]. Analogously, many studies showed that the postoperative use of braces after ACLR was not beneficial for the outcome nor for early rehabilitation [ 13 , 22 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 59%
“…Rather, early weight bearing seemed to improve the quadriceps muscle function and reduce the risk for patellofemoral pain [ 21 , 23 , 29 , 30 ], which is particularly associated with the choice of BTB grafts [ 6 , 10 ]. However, the DGOU tend to delay full weight bearing after ACLR for two weeks, similar to the survey’s results (ACLR-HAM: 2.0 ± 1.1 weeks; ACLR-BTB: 1.2 ± 0.7 weeks) [ 19 , 31 ], whereas the MOON Guidelines recommend immediate weight bearing after ACLR and so does the KNGF, as long as the gait pattern is correct [ 21 , 22 ]. Analogously, many studies showed that the postoperative use of braces after ACLR was not beneficial for the outcome nor for early rehabilitation [ 13 , 22 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 59%
“…Während innerhalb der Behandlung nach einer Rekonstruktion des vorderen Kreuzbandes ein frühes Training im offenen System und eine orthesenfreie Nachbehandlung empfohlen wird 1 , 17 , 29 , ermittelt die Befragung der Mitglieder der Deutschen Kniegesellschaft einen konträren Ist-Zustand. In 82 Prozent der Fälle wird eine Empfehlung „pro“ Orthese gegeben 28 . Evidenzbasierte Nachbehandlungsprotokolle scheinen daher mehr ein frommer Wunsch als reale Praxis zu sein.…”
Section: äRztliche Gesellschaften Legen Fehlende Evidenzbasierte Empf...unclassified
“…Beginn der Mobilisation der Schulteraußenrotation ab der 4. Woche nach einer Bankart-Operation, Joggen nach einer Rekonstruktion des vorderen Kreuzbandes nach 3 Monaten) [11] [54]. Ein solcher Ansatz kann durchaus begründet sein.…”
Section: Hintergrundunclassified
“…Ein zeitbasiertes Schema hat insbesondere dann eine Bedeutung, wenn es sich an einer verringerten Belastung traumatisierter Strukturen im Rahmen der Wundheilung orientiert. Leider zeigen Übersichtsarbeiten aber, dass bei gleicher Operationsmethode völlig unterschied-licheVorgabenbestehen[6] [11] [53] [54].Offensichtlich stehen daher weniger physiologische Prinzipien, sondern eher persönliche Präferenzen von Ärzten und Therapeuten im Vordergrund.…”
Section: Hintergrundunclassified